1984
DOI: 10.1111/j.1399-3011.1984.tb00933.x
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of human mercapt‐ and nonmercaptalbumin by high‐performance liquid chromatography

Abstract: Gel-exclusion high-performance liquid chromatographic (HPLC) analysis of human serum albumin (HSA) on PGP 2000 column ( 0 . 1 0~ sodium phosphate buffer, 0.30~ NaCl, pH 6.86) showed at least two peaks, the principal component corresponding to human mercaptalbumin (HMA) and the second one t o human nonmercaptalbumin (HNA). Mechanism for the separation of HMA and HNA might be due to weak resin-HSA interaction. HPLC analysis of bovine plasma albumin (BPA) showed a single peak on PGP 2000 column. The elution volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(45 citation statements)
references
References 39 publications
2
43
0
Order By: Relevance
“…The Cys-34 of HSA makes up approximately 80% of the total free thiol content in plasma [15] and the state of Cys-34, i.e., the redox state of HSA, is thus indicative of the degree of short-term systemic oxidative stress because of the short half-life (*20 days) of the albumin molecule [15]. We have developed a convenient high-performance liquid chromatography (HPLC) system for the clear separation of HSA into HMA and HNA [16,17], and we have extensively studied the dynamic changes of HSA(Cys-34)-redox state under various physiologic [18][19][20] and pathophysiologic states, such as hepatic [21,22], renal [5,[23][24][25][26], diabetic [27], and other diseases [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The Cys-34 of HSA makes up approximately 80% of the total free thiol content in plasma [15] and the state of Cys-34, i.e., the redox state of HSA, is thus indicative of the degree of short-term systemic oxidative stress because of the short half-life (*20 days) of the albumin molecule [15]. We have developed a convenient high-performance liquid chromatography (HPLC) system for the clear separation of HSA into HMA and HNA [16,17], and we have extensively studied the dynamic changes of HSA(Cys-34)-redox state under various physiologic [18][19][20] and pathophysiologic states, such as hepatic [21,22], renal [5,[23][24][25][26], diabetic [27], and other diseases [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…the redox state of albumin, is thus indicative of the degree of systemic OS. We have developed a high-performance liquid chromatographic (HPLC) system for the clear separation of HSA into HMA and HNA [7] , and we have extensively studied the mercapto-nonmercapto conversion of HSA under various physiological and pathophysiological states [5-7, 9-11, 14-19] .…”
Section: Introductionmentioning
confidence: 99%
“…Human nonmercaptoalbumin (HNA; oxidized) is present in a disulfide that is formed reversibly with Cys or glutathione, or as an oxide that is formed irreversibly such as in a sulfinic acid, sulfonic acid, or a similar structure. 13 Interestingly, in the past 10 years, it has been shown that HMA and HNA occur in equilibrium, depending on the surrounding redox state, and that their ratio varies depending on the age and the diseased state. [14][15][16] In a previous study, using high-performance liquid chromatography (HPLC), we monitored the redox state of the 34 Cys residue of HSA and showed that an overdosing of intravenous iron in the treatment of anemia in HD patients results in an intensification of oxidative stress in the blood.…”
Section: Introductionmentioning
confidence: 99%